The Role of Materials Science in the Development of Health Tourism in East Kazakhstan (Journal of Geography and Environmental Management, 2024)
In recent years, due to the development of domestic tourism in East Kazakhstan, there has been a great interest in wellness services based on the use of antler raw materials. The creation of special economic zones of tourist and recreational type on the territory of East Kazakhstan gives impetus to the development of maral breeding. The active development of tourism significantly expands the use of therapeutic and health technologies based on products of antler reindeer husbandry.The article notes that one of the most important prerequisites for the transformation of the East Kazakhstan region into a sanatorium-resort area is the development of treatment centers with maral antlers. On its basis, the analysis of the recreational resources of the region is carried out and the current state is considered. The main purpose of the study is to bring the health tourism of East Kazakhstan to the world level by treating maral antlers. The study tells about the main role of marals in the development of medical tourism in East Kazakhstan and its huge benefits for human health. It is determined in which territory of the region they predominate and is evaluated on the example of the Altai Territory as an object of research. The current state of the maral processing centers on the territory of the research object is covered in detail, the main causes of the problems that have arisen are identified, recommendations and solutions are given. The research was carried out by methods of observation, analysis, relying on documents and statistical data.
Keywords: еast Kazakhstan, maral, рantоthеraру, tоurіsm, hеalth tоurіsm, sanatоrіum, rеsоrt, rесrеatіоn.